The Effect of the Project Based Learning Model Assisted by Media Explosion Box on the Learning Outcomes of Class V Students of SDN Pinggir Papas 1 - Alfiatul Khoiriyah; Syaiful Bahri; Zainuddin Zainuddin (SAINTIS Publishing, 2025)
This research aims to find out whether there is an influence of the project based learning model assisted by explosion box media on the science learning outcomes of elementary school students. This research uses a type of quantitative research with a pre-experimental method with a one group pretest posttest design research design. Data collection techniques used tests. The population in this study was all 23 students in class V of SDN Pinggir Papas 1, Kalianget District. The instruments used are multiple choice tests. The average score from the pretest was 44.35, while the posttest score was an average of 80.78. The results of the research for hypothesis testing using the paired samples test statistical test, obtained I a significance value of 0.05, namely 0.000, then Ho was rejected and Ha was accepted. Therefore, it can be concluded that these results show that there is an influence of the project based learning model assisted by explosion box media on students' science learning outcomes.